Preferential transposition of the maize element Activator to linked chromosomal locations in tobacco. - Jones, J D (1990)
The autonomous maize transposon Activator (Ac) has been used in maize for gene isolation by tagging and may prove similarly useful in other species. To test the feasibility of gene tagging with heterospecific transposons, we have examined three key genetic properties of a slightly modified Ac in tobacco. First, we show that frequencies of germinal excision of this Ac element from the antibiotic resistance gene streptomycin phosphotransferase can be comparable with or slightly lower than in maize. Second, we show that about half of the progeny carrying a germinal excision product also carry a transposed Ac. Last, we have mapped transposed Ac locations relative to the streptomycin transferase gene excision product and have shown that as in maize Ac in tobacco preferentially transposes to genetically linked sites.